Effect of Natural Antioxidant Supplementation of Rose Cider (Rosa damascena) on Oxidative Stress in High-Risk Pregnant Women: An Analysis of Malondialdehyde (MDA) Biomarkers - Laila, Ani; Alyensi, Fatiyani; Pertiwi, Riana (Journal of Health and Nutrition Research, 2025)
Pregnancy in high-risk mothers is often linked to increased oxidative stress, which can cause obstetric complications and impair fetal development. Malondialdehyde (MDA), a byproduct of lipid peroxidation, is a commonly used biomarker to assess oxidative stress levels. Nutritional interventions based on natural antioxidants are gaining attention as a strategy to reduce oxidative stress during pregnancy. Rose cider (Rosa damascena) contains phenolic compounds and flavonoids with antioxidant properties. This study aimed to evaluate the effect of rose cider supplementation on MDA levels in high-risk pregnant women. A quasi-experimental design with a pretest-posttest measurements was conducted involving 60 high-risk pregnant women randomly assigned to two groups: the intervention group received 250 ml of rose cider daily for 30 days, while the control group received a placebo. MDA levels were measured before and after the intervention using the thiobarbiturate (TBA) spectrophotometry method. Results showed a significant reduction in MDA levels in the intervention group compared to the control group (p < 0.01). The intervention group’s MDA decreased by 1.87 ± 0.45 μmol/L, whereas the control group’s reduction was only 0.42 ± 0.31 μmol/L. These findings demonstrate the effectiveness of antioxidant compounds in rose cider in lowering oxidative stress among high-risk pregnant women. This supports the potential of herbal-based supplements as preventive measures in managing high-risk pregnancies. Further research is recommended to explore the long-term effects and molecular mechanisms underlying this supplementation.